2019
DOI: 10.1108/er-03-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Support for supervisors: HR enabling flexible work

Abstract: Purpose Flexible work arrangements (FWAs) are routinely offered in organizational policy, yet employee access to FWAs is highly dependent upon support from their immediate supervisor. There is little empirical research that specifically investigates the role of the human resource function (HR) in supporting managers to implement FWA policy. Through the lens of HR systems theory, the purpose of this paper is to examine how HR supports managers to implement FWAs. Design/methodology/approach Using a case study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The first author wrote memos to decipher whether an issue linked to threat, opportunity or mixed and then looked for linguistic evidence of distributive or integrative approaches to issues. Similar to other qualitative research (Najeeb and Barrett, 2019; Payne and Fisher, 2019; Williams, 2019), we used the words of participants to give them voice regarding our research claims about the issues, characteristics, interpretations and approaches.…”
Section: Methodsmentioning
confidence: 99%
“…The first author wrote memos to decipher whether an issue linked to threat, opportunity or mixed and then looked for linguistic evidence of distributive or integrative approaches to issues. Similar to other qualitative research (Najeeb and Barrett, 2019; Payne and Fisher, 2019; Williams, 2019), we used the words of participants to give them voice regarding our research claims about the issues, characteristics, interpretations and approaches.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, middle managers act as a vital “organisational lubricant” (Cooper & Baird, 2015, p. 570), translating organizational policy into practice (den Dulk & de Ruijter, 2008; Maxwell, 2005). Many studies have examined the role of middle managers in the implementation of specific components of gender equality policy—such as facilitating flexible work (see, e.g., Bond & Wise, 2003; Cooper & Baird, 2015; Stout, Awad, & Guzmán, 2013; Williams, 2019) but fewer studies have examined middle mangers' role in supporting or hindering the progress of gender equality policies more generally (Kelan & Wratil, 2018).…”
Section: Middle Managers' Role In Progressing Gender Equalitymentioning
confidence: 99%
“…FWA research have showed that supervisors and managers must believe in the benefits that FWAs can bring. FWAs demand new ways of thinking about the work being carried out and handled, the position of supervisors becomes increasingly complex but with the easy access to advice and guidance from HR consultants, some of the challenges can be resolved by having clearer views between policy and action (Williams, 2019). This will allow companies to meet the challenges of retaining skilled, hard-working and dedicated workers.…”
Section: Human Resource Researchmentioning
confidence: 99%